Nutritional Epidemiology Study: Prevalence of Vitamin and Mineral Supplement Use and Correlated Factors among University Students in Jordan - Ibrahim, Mohammed O. (Pakistan Journal of Nutrition, 2018)
Objective: This study was carried out to determine the prevalence and associated factors of vitamin-mineral supplements use among University students. Methods: A cross-sectional study applied a quantitative research approach using a self- administrated questionnaire given to University students in Jordan. Results: The prevalence of vitamin-mineral supplement use was 23%. The main reasons for using vitamin mineral supplements were ‘to maintain good health’ (73%), followed by ‘to lose weight’ (11%). Vitamin-mineral supplement use among participants was significantly (p<0.05) associated with gender, age, BMI, family monthly income, physical activity, smoking status and vegetarian status. The main source of information of supplement use was doctors (60.5%). "Maintaining good health" was the most frequently given reason for using supplements (73%). The major frequently used supplements were vitamin only supplements (51.5%), followed by vitamin-mineral combinations supplements (44%). Conclusion: This study highlighted that although the prevalence of vitamin-mineral supplement use among university students is relatively high, many of them do not have accurate information about supplements. Therefore, there is a need to provide them with education and access to scientific and unbiased information.